Ectoparasites of the black-chinned siskin Spinus barbatus (Passeriformes: Fringillidae) in Chile - Fuentes Castillo, Danny (2016)
Despite being a bird with a broad and extensive distribution in Chile, the black-chinned siskin, Spinus barbatus Molina, 1782 is not well studied in relation to its parasites. This paper aims to describe the ectoparasite fauna of S. barbatus in central and southern Chile. A total of 125 individuals caught with mist nets were examined alive; a total of 22 parasites were found dead and were exposed to parasit autopsy. The extracted parasites were preserved in 70% alcohol for subsequent mounting and identification. Ectoparasites were found in 56 black-chinned siskins (38%); 48 of them (33%) had 870 mites – 680 feather mites (Astigmata: Analgoidea) were identified as Proctophyllodes spini, 167 as Knemidokoptes jamaicensis, 19 as Strelkoviacarus critesi, and one as Analges passerinus. Moreover, three mites were chiggers belonging to the tribe Schoengastiini (Prostigmata: Trombiculidae). In 21 birds (14%), 54 lice were found, 21 of which were identified as Philopterus roehreri, 18 as Myrsidea serini, and 15 as Ricinus carolynae. Endoparasites were not found in the necropsied individuals. All of the parasites that were found represent new records for Chile, and they also serve as new records of host–parasite associations for S. barbatus.